Implementation of the Peer Assessment Model in Mathematics Learning Evaluation: An Innovative Approach - Dewi, Puspita; Elfrianto, Elfrianto (EDUCTUM: Journal Research, 2024)
This research explores the implementation of a peer assessment model for evaluating mathematics learning as an innovative approach to enhance student understanding and classroom dynamics. Using qualitative methods, the study employs classroom observations, document analysis, and interviews with teachers and students to assess the impact of the model. Results indicate that the peer assessment model fosters student collaboration in the mathematics teaching and learning process. Improved social interaction positively influences concept understanding, with students actively contributing to building collective knowledge. Despite increasing student engagement, challenges such as unequal comprehension levels and the need for additional teacher support were identified. Adaptation for effective integration into the existing mathematics curriculum is necessary, considering students' individual differences. The research affirms that the peer assessment model not only gauges students' final understanding but also underscores the learning process itself. Emphasizing the development of interpersonal and collaboration skills leads to a dynamic learning environment. Consequently, this study recognizes the potential of the peer assessment model as an innovative evaluation tool in mathematics learning. Although adjustments and addressing emerging challenges are required, the model holds promise for significant changes in the evaluation and teaching of mathematics, contributing to a more holistic and contextual approach to learning.